Amelioration of diethylnitrosamine (DEN)-induced hepatocellular carcinogenesis in animal models via knockdown oxidative stress and proinflammatory markers by Madhuca longifolia embedded silver nanoparticles. Issue 13 (12th February 2018) - Singh, Deepika; Singh, Manvendra; Yadav, Ekta; Falls, Neha; Komal, Ujendra; Dangi, Deependra Singh; Kumar, Vikas; Verma, Amita
Abstract : In hepatocellular carcinoma (HCC), primary liver cancer is primarily responsible for inflammation-related cancer as more than 90% of HCCs emerge with regard to hepatic damage and inflammation. Abstract : In hepatocellular carcinoma (HCC), primary liver cancer is primarily responsible for inflammation-related cancer as more than 90% of HCCs emerge with regard to hepatic damage and inflammation. Tenacious inflammation is known to advance and intensify liver tumours. Nanomaterials, for example, silver nanoparticles synthesized from plant-derived materials have shown great outcomes in reducing the pre-cancerous nodules and have anticancer properties. The aim of the present investigation was to biosynthesize, characterize and evaluate the anticancer activity of nanoparticles-embedded Madhuca longifolia extract (MLAgNPs) on an experimental model of hepatic cancer in rats. M. longifolia contains a high amount of flavonoids and other phenolic derivative. The silver nanoparticles synthesized by M. longifolia were characterized by various instruments, including UV-Vis spectrophotometry, X-ray beam diffraction, field-emission scanning electron microscopy with energy dispersive X-ray analysis, transmission electron microscopy and Fourier transform infrared spectroscopy. Liver cancer was induced to 36 Wistar rats by a single dose of diethylnitrosamine (DEN) (200 mg kg −1 BW). Hepatic cancer by MLAgNPs dose-dependently limited macroscopical variation compared with the DEN-induced hepatic cancer groups. The serum and liver were taken to measure the antioxidant parameters, proinflammatory cytokines and for a histopathological study. Serum hepatic and serum non-hepatic along with inflammatory cytokines were also assessed. Reduction in the levels of proinflammatory cytokines, namely tumour necrosis factor-α, interleukin-6, interleukin-1β, nuclear factor kappa beta (NF-κB), and improved membrane-bound enzyme activity were also detected. It was found that minor morphological anomalies were identified in the histopathology analysis in the MLAgNPs-treated groups. It could be concluded that silver nanoparticles introduce an extraordinary potential for use as adjuvants in hepatic cancer treatment because of their antioxidant abilities and ability to diminish inflammation in liver tissue by attenuating the NF-κB pathway.